The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.5539/elt.v8n5p195
|View full text |Cite
|
Sign up to set email alerts
|

Does E-Reading Enhance Reading Fluency?

Abstract: Extensive reading is reading as much as possible, for one's own pleasure, at a difficulty level at which one can read smoothly and quickly. In the domain of reading, this paper investigates the effect of extensive reading from e-books, through utilizing a number of downloadable reading application programs on the students' e-devices, as opposed to traditional book-reading in an ESL context. It aims at providing answers as to how e-book reading affects the students' reading rate, their reading comprehension, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…Silent reading helps students to be more focused on their reading process. Silent reading maintains the reader's concentration on reading longer text (Hiebert et al, 2014, p. 8;Akbar et al, 2015). 8) Reading is its reward.…”
Section: The Implementation Of Extensive Readingmentioning
confidence: 99%
“…Silent reading helps students to be more focused on their reading process. Silent reading maintains the reader's concentration on reading longer text (Hiebert et al, 2014, p. 8;Akbar et al, 2015). 8) Reading is its reward.…”
Section: The Implementation Of Extensive Readingmentioning
confidence: 99%
“…The other studies were survey study (Nie, Armellini, Witthaus, & Barklamb, 2011;Rogerson-Revell, Nie, & Armellini, 2012) and research and development (Hussain & Al Saadi, 2019;Wu, 2016). The e-books provide language learners with useful multimedia features that can enhance vocabulary, reading comprehension, reading rate and listening comprehension (Akbar et al, 2015;Chen et al, 2013;Hsieh & Huang, 2020;Leacox & Jackson, 2014;Liu et al, 2019;Wood et al, 2018;Wu, 2016;Yow & Priyashri, 2019).…”
Section: E-book In English Language Teachingmentioning
confidence: 99%
“…One of products of such technology integration in instructional design is e-books. E-books, in English language teaching context, help both learners and teachers to have an interactive teaching and learning environment that triggers learning motivation (Almunawaroh, 2020), develop learners" reading comprehension (Yow & Priyashri, 2019) and listening comprehension (Hsieh & Huang, 2020), increase learners" reading speed (Akbar, Taqi, Dashti, & Sadeq, 2015), and accelerating vocabulary (Leacox & Jackson, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Akbar et al (2015) surveyed 40 freshman female students studying in the College of Basic Education in the English department, PAAET, Kuwait. Data drawn from students' writing diaries together with two questionnaires were analyzed both quantitatively and qualitatively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Spencer (2006) reported negative aspects of e-reading in an academic setting. Akbar, Taqi, Dashti, and Sadeq (2015) investigated e-reading usage as opposed to traditional book reading in Kuwait and highlighted the fact that e-reading may accelerate students' reading rate and progress, but they also cautioned that there might be a lower level of comprehension when reading e-resources. The authors concluded that students' attitudes toward e-reading tended to be less positive than toward conventional book reading.…”
Section: Introductionmentioning
confidence: 99%